2017
DOI: 10.1002/jmri.25859
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast‐enhanced MRI in orbital lymphoproliferative disorders: Effects of region of interest selection methods on time efficiency, measurement reproducibility, and diagnostic ability

Abstract: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1298-1305.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In agreement with previous studies [1,2,4,18,19], we found that orbital lymphoma has a male predominance and most orbital lymphomas were MALT lymphoma. In agreement with results of other investigators, the age of patients with orbital lymphoma was significantly higher than those with inflammatory mass [1,3,15].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with previous studies [1,2,4,18,19], we found that orbital lymphoma has a male predominance and most orbital lymphomas were MALT lymphoma. In agreement with results of other investigators, the age of patients with orbital lymphoma was significantly higher than those with inflammatory mass [1,3,15].…”
Section: Discussionsupporting
confidence: 93%
“…However, Braunagel et al [17] reported that there were no significant differences on the quantitative parameters when different ROI selection methods were used. Qian et al [3] compared the quantitative parameters' diagnostic performance and also no significant differences were found. Similarly in our study, the two methods of selecting ROI showed no significant difference in distinguishing lymphoma from inflammatory mass of orbit.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations